IoT Based Smart Parking for Metro Cities - Joshi, A; Kharade, KS; Patil, VS; Kulkarni, DA (International Journal of Computer Sciences and Engineering, 2025)
An emerging technology aiming to connect the surrounding environmental things to the network and making the access to the same in a very easy way is Internet of Things- IOT. The paper focuses on the same technology which is useful for identifying, disseminating the known facts and connect the entire world under a single system. The work here creates an android application for providing a parking solution to smart cities. This literature aims to resolve the parking issues and other related problems as traffic, pollution, over fuel consumption etc. by public involvement. This application holds good for both public and government as well which in turn helps decrease congestions on roads.